Factors Influencing Work-Life Balance in Physicians and Advance Practice Clinicians and the Effect of Heartfulness Meditation Conference on Burnout - Jayaram R Thimmapuram MD; Rodney Grim PhD; Theodore Bell MS; Ronald Benenson MD; Mark Lavallee MD; Mihir Modi DO; David Noll DO; Ridgley Salter MD (SAGE Publishing, 2019)
Background Burnout levels have risen in recent years and satisfaction with work-life balance has decreased. Individual and organizational factors may affect burnout in physicians and advance practice clinicians (APCs). Meditation is a tool to mitigate stress and enhance well-being. In this study, we assessed the factors affecting work-life balance in physicians and APCs. We also measured the impact of Heartfulness meditation conference on burnout. Methods Physicians and APCs were surveyed through an abbreviated Maslach burnout inventory (aMBI) to assess the burnout levels and a question to assess the factors influencing work-life balance. Wellness initiatives included either attending a Heartfulness meditation conference or reading a book about burnout and wellness (approximated at a 3-h read). A repeat aMBI survey was sent 8 weeks after the conference. Pre- and postburnout scores were assessed. Results Of the 1393 physicians and APCs, 537 responded to the aMBI, and there were 414 comments (663 factors) for the question on work-life balance. Among the respondents, 60.5% and 32% had symptoms of moderate to severe emotional exhaustion (EE) and depersonalization, respectively. Twenty-eight percent of the respondents had symptoms of moderate to low personal accomplishment. The major factors impacting work-life balance included work load, work flow, and scheduling. A follow-up aMBI survey was completed by 79 from the conference group and 264 from the nonconference group. In the age-group between 30 and 50 for the conference group (n = 40), mean EE decreased from 9.8 to 8.6 with statistical significance ( P  = .014). There was no statistically significant change in the nonconference group in any age-group. Conclusion Workload, workflow, and scheduling issues were the major factors affecting work-life balance. There is a significant level of burnout in physicians and APCs. Heartfulness meditation conference was associated with a significant decrease in EE in those aged 30 to 50 years. There was no significant change seen in the nonconference/book reading group.